Microwave assisted extraction of phenolic compounds from four economic brown macroalgae species and evaluation of their antioxidant activities and inhibitory effects on α-amylase, α-glucosidase, pancreatic lipase and tyrosinase - Yuan, Yuan; Zhang, Jian; Fan, Jiajun; Clark, James; Shen, Peili; Li, Yiqiang; Zhang, Chengsheng (Food research international, 2018)
Four economically important brown algae species (Ascophyllum nodosum, Laminaria japonica, Lessonia trabeculate and Lessonia nigrecens) were investigated for phenolic compound extraction and evaluated for their antioxidant, anti-hyperglycemic, and pancreatic lipase and tyrosinase inhibition activities. Microwave assisted extraction (MAE) at 110 °C for 15 min resulted in both higher crude yield and higher total phenolic content (TPC) for all algae species compared with those obtained by conventional extraction at room temperature for 4 h, and Ascophyllum nodosum yielded the highest TPC. Antioxidant tests indicated that extracts acquired by MAE from four species all exhibited higher DPPH, ABTS free radical scavenging ability and reducing power than the conventional method. The extract of Lessonia trabeculate exhibited good α-amylase, α-glucosidase, pancreatic lipase, and tyrosinase inhibition activities, and the MAE extract showed even better α-glucosidase inhibitory activity than acarbose. [Display omitted] •Polyphenols were effectively extracted by microwave assisted extraction.•Extracts of Ascophyllum nodosum showed good antioxidant activities.•Four enzymes were inhibited in vitro by brown macroalgae polyphenol extracts.•Extracts of Lessonia trabeculate showed inhibitory activities in all four enzymes.•Extracts of Lessonia trabeculate had better α-glucosidase inhibition than acarbose.